Determination of Interest Rate in Nepalese Finance Companies - Ojha, Bhoj Raj (Management Dynamics, 2020)
Finance companies are the institutions that are incorporated under company act to perform non-banking activities arrangements and operation of different schemes. The finance companies survive by making profit which is the interest spread i.e. difference between interest received and interest charged. The main aim of this paper was to determine the responsible factors for the interest rate determination of Nepalese financial companies. The factors affecting interest rate charged and offered by Nepalese financial companies are analyzed using Regression Analysis. Out of the total financial companies only two ICFC Finance Company and United Finance Company are taken as samples. Secondary data are collected from various publications, websites, and annual reports. Interest rate on deposit of ICFC Finance has significant negative association with inflation rate and significant positive relation with interest rate on loan and advance of the company. Similarly, interest rate on loan and advance of the company has significant positive relation with interest rate on deposit and interest rate on loan and advance also has positive relation with inflation rate. Interest rate on deposit of United Finance has significant negative association with inflation rate and significant positive relation with interest rate on loan and advance of the company. Similarly, interest rate on loan and advance of the company has significant positive relation with both interest rate on deposit and inflation rate.